2001
DOI: 10.1163/156853801317050106
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive behaviour of the Chinhai Salamander (Echinotriton chinhaiensis) (Caudata: Salamandridae)

Abstract: Abstract. The Chinhai Salamander, Echinotriton chinhaiensis, mates on land. The male of a courting pair marks a trail by a mucous excretion from his cloaca. The pair follows an ellipsoid track during which manoeuvre a spermatophore is deposited. Partners align their bodies such that the female is led over the spermatophore. Clasping was not observed. The female traces the spermatophore with her cloaca through shifting movements with the pelvic region. A male may deposit several spermatophores on one evening. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 13 publications
2
14
1
Order By: Relevance
“…However, the male indiscriminately exhibited courtship behavior toward females from different localities. Sparreboom et al (2001), on the basis of captive observations, reported mating behavior of T. (E.) chinhaiensis, which was basically similar to that reported here for T. (E.) andersoni with respect to the male behavior up to the stage of spermatophore deposition. In both species, for example, the male, after sniffing the female, marks a trail around her by excreting mucous from his cloaca, and finally deposits the spermatophore without clasping her.…”
Section: Spermatophore Morphologysupporting
confidence: 85%
See 4 more Smart Citations
“…However, the male indiscriminately exhibited courtship behavior toward females from different localities. Sparreboom et al (2001), on the basis of captive observations, reported mating behavior of T. (E.) chinhaiensis, which was basically similar to that reported here for T. (E.) andersoni with respect to the male behavior up to the stage of spermatophore deposition. In both species, for example, the male, after sniffing the female, marks a trail around her by excreting mucous from his cloaca, and finally deposits the spermatophore without clasping her.…”
Section: Spermatophore Morphologysupporting
confidence: 85%
“…In both species, for example, the male, after sniffing the female, marks a trail around her by excreting mucous from his cloaca, and finally deposits the spermatophore without clasping her. Like male T. (E.) andersoni, male T. (E.) chinhaiensis may deposit several spermatophores in one evening (Sparreboom et al, 2001). Sparreboom et al (2001) observed the trailmarking by mucous excretion from the male's cloaca in T. (E.) chinhaiensis, and assumed the behavior to be a remarkable feature of this species.…”
Section: Spermatophore Morphologymentioning
confidence: 96%
See 3 more Smart Citations